SOSIALISASI UJI KANDUNGAN BAHAN MAKANAN DI SMP N 2 AMANUBAN SELATAN PROVINSI NUSA TENGGARA TIMUR - Hildegardi Missa; Eduardus Johanes Eduk Johanes Eduk; Aloysisu Djalo; Anselmus Boy Baunsele (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The purpose of conducting this food content test activity is to increase the knowledge of students and teachers about the content of food consumed in daily life, as well as to determine the content of food consumed in everyday life.This service activity was carried out at Junior High School 2 South Amanuban and the participants of the activity were 46 students and teachers at the school. This activity is carried out by preparing tools and materials to be used for socialization, initial simulation before carrying out socialization, material exposure, testing the content of food ingredients, observing results, providing information about substances contained in food ingredients that are consumed daily and Reporting.The results of this outreach activity based on questionnaires that were written by students showed that 100% of Middle School 2 Amanuban Selatan students were able to define the meaning of food, and describe the types of local food in the area where they lived, were able to explain the content of substances in local food in the Kuanfatu area and able to follow food testing activities well.